Antimicrobial activity of adipose-derived mesenchymal stromal cell secretome against methicillin-resistant Staphylococcus aureus - Fatimah Shaaban; Elie Salem Sokhn; Charbel Khalil; Fatima A. Saleh (Stem Cell Research & Therapy)
Abstract Background Methicillin-resistant Staphylococcus aureus (MRSA) is still a growing concern in the field of antimicrobial resistance due to its resistance to conventional antibiotics and its association with high mortality rates. Mesenchymal stromal cells (MSCs) have been shown as a promising and attractive alternative treatment for bacterial infections, due to their antibacterial properties and potential to bypass traditional resistance mechanisms. This study aims to shed light on the antibacterial potential of adipose-derived mesenchymal stromal cell (AD-MSC) secretome against clinical isolates of Staphylococcus spp., including MRSA strains. Methods Using the Kirby-Bauer disk diffusion method, broth microdilution assays, and colony-forming unit (CFU) counting, the antibacterial activity of AD-MSC secretome was assessed. These tests were first conducted on Staphylococcus (S.) aureus ATCC 25923, then on 73 clinical isolates including MRSA strains. Further molecular analysis was performed to identify resistant genes in MRSA isolates. Results The AD-MSC secretome demonstrated significant antibacterial activity against S. aureus ATCC with a 32 mm inhibition zone. 96% of the collected staphylococcal clinical isolates showed susceptibility to the secretome with 87.5% inhibition observed in MRSA isolates, along with 100% in MSSA, MSSE, and MRSE strains. Molecular analysis revealed that MRSA strains resistant to the secretome harbored mecA, ermA, and ermB genes. Additionally, the mecA-negative MRSA strains remained susceptible to the secretome, suggesting alternative resistance mechanisms. Conclusion These findings emphasize the ability of AD-MSCs secretome as a promising alternative for treating antibiotic-resistant infections, with potential applications in combating MRSA. However, further research is required to explore its clinical applications as a complementary or standalone therapy for resistant infections.